Fundamentals of web development - Connolly, Randy, ....-; Hoar, Ricardo, ....- (Boston : Pearson, 2015)
Fundamentals of Web Development covers the broad range of topics required for modern web development (both client- and server-side) and is appropriate for students who have taken a CS1 course sequence. The book guides students through the creation of enterprise-quality websites using current development frameworks. It covers the required ACM web development topics in a modern manner closely aligned with best practices in the real world of web development.